1996
DOI: 10.1177/0310057x9602400501
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia following Thoracotomy: A Survey of Australian Practice

Abstract: This survey examines pain management after thoracotomy in Australian hospitals. Questionnaires were sent to senior thoracic anaesthetists at 27 hospitals (16 public and 11 private) with thoracic surgical units. Twenty-six anaesthetists replied and 24 responses were included in the analyses. Seventy-two percent of respondents were from hospitals with acute pain services (APS), and in 94% of these hospitals patients are reportedly visited by the APS. The most frequently used analgesic modalities are epidural ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…A survey of analgesic techniques, after thoracotomy, in Australian hospitals showed that 79% of respondents regarded epidural blockade as the best available technique. 2 A similar survey in the United Kingdom by Cook and Eaton 7 showed that epidural analgesia was the most frequently used form of regional analgesia technique used after thoracotomy. Although epidural analgesia was the favoured technique used by nearly half of the respondents, paravertebral blocks combined with PCA morphine is fast gaining acceptance as a viable alternative to epidural analgesia in open thoracotomy procedures (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A survey of analgesic techniques, after thoracotomy, in Australian hospitals showed that 79% of respondents regarded epidural blockade as the best available technique. 2 A similar survey in the United Kingdom by Cook and Eaton 7 showed that epidural analgesia was the most frequently used form of regional analgesia technique used after thoracotomy. Although epidural analgesia was the favoured technique used by nearly half of the respondents, paravertebral blocks combined with PCA morphine is fast gaining acceptance as a viable alternative to epidural analgesia in open thoracotomy procedures (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…It must provide good analgesia during deep breathing and movement to allow coughing and physiotherapy. 2 Epidural analgesia has long been considered as the 'gold standard' among regional anaesthetic techniques for providing pain relief after thoracotomy. A survey of analgesic techniques, after thoracotomy, in Australian hospitals showed that 79% of respondents regarded epidural blockade as the best available technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of Australian thoracic anaesthetists in 1997 revealed that 79% regarded TEB as the method of choice for analgesia in thoracotomy 15. Similar results were found in the UK with 80% of anaesthetists considered TEB as the best mode of pain relief for upper abdominal surgery 16.…”
Section: Introductionmentioning
confidence: 83%
“…[19] A similar survey of UK practice, after upper abdominal surgery, found that 80% of anesthetists considered epidural analgesia to be the best mode of pain relief. [20] Researchers have shown thoracic PVB to be an effective form of analgesia after thoracotomy.…”
Section: Discussionmentioning
confidence: 99%